2015
DOI: 10.1371/journal.pone.0127647
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Energy Under-Reporting on Secular Trends of Dietary Patterns in a Mediterranean Population

Abstract: BackgroundDiet is an important factor in the prevention of chronic diseases. Analysis of secular trends of dietary patterns can be biased by energy under-reporting. Therefore, the objective of the present study was to analyse the impact of energy under-reporting on dietary patterns and secular trends in dietary patterns defined by cluster analysis.Design and methodsTwo cross-sectional population-based surveys were conducted in Spain, in 2000 and 2005, with 3058 and 6352 participants, respectively, aged 25 to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 41 publications
1
8
0
Order By: Relevance
“…Studies using the DLW method have clearly shown that all dietary assessment methods tend to underestimate EI to various degrees (57)(58)(59) . Previous studies have reported prevalence of low energy reporting ranging from 10 to 60 % depending on the dietary assessment method, the reference method used to identify low energy reporters and the characteristics of the study population (4,11,58,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) . In the revised Goldberg cut-off equations (10) , the individual's physical activity is taken into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies using the DLW method have clearly shown that all dietary assessment methods tend to underestimate EI to various degrees (57)(58)(59) . Previous studies have reported prevalence of low energy reporting ranging from 10 to 60 % depending on the dietary assessment method, the reference method used to identify low energy reporters and the characteristics of the study population (4,11,58,(60)(61)(62)(63)(64)(65)(66)(67)(68)(69)(70)(71)(72) . In the revised Goldberg cut-off equations (10) , the individual's physical activity is taken into account.…”
Section: Discussionmentioning
confidence: 99%
“…A few studies have investigated the effect of under-reporting on empirically derived dietary patterns (11)(12)(13)(14)(15)(16)(17)(18) ; four studies have reported that the composition of food groups that significantly contributed to the dietary patterns remained relatively unchanged after removal of low energy reporters (11,(13)(14)(15) . One study found that the number of dietary patterns differed between plausible reporters and all reporters (12) .…”
mentioning
confidence: 99%
“…A further limitation of our study is the widely acknowledged under-reporting of energy intake from self-reported dietary assessment methods 23 . It is well-known that energy underreporting of foods is selective, with unhealthy and snack foods more likely to be forgotten during dietary reporting 31,32 . Although this may potentially bias the analysis of dietary patterns, it is likely that recall error in our study was similar for case and control participants.…”
Section: Most Of the Limited Dietary Research In Relation To Ms Has Bmentioning
confidence: 99%
“…The influence of underreporting of energy intake on dietary patterns determined by the clusters method were more prevalent in groups described as healthy [33,34] and the exclusion of these individuals did not alter the contribution of the food group in the description of the cluster. However, by excluding under-reporters, the patterns described as mixed and western showed a high consumption of unhealthy food groups such as sausages, white bread, pastry, soft drinks and fast foods by plausible reporting participants [34].…”
Section: Discussionmentioning
confidence: 90%
“…While the exclusion of information of a high percentage of under-reporting patients contributed to a new conformation of dietary patterns, the exclusion of a low percentage of under-reporting patients (16.3%) did not induce variations in the definition of dietary patterns, but in different contributions from certain food subgroups described in plausible reporters patterns [32]. The influence of underreporting of energy intake on dietary patterns determined by the clusters method were more prevalent in groups described as healthy [33,34] and the exclusion of these individuals did not alter the contribution of the food group in the description of the cluster. However, by excluding under-reporters, the patterns described as mixed and western showed a high consumption of unhealthy food groups such as sausages, white bread, pastry, soft drinks and fast foods by plausible reporting participants [34].…”
Section: Discussionmentioning
confidence: 91%